The Role of the Welfare State in Regulating Marketplace Policies to Protect the Sustainability of Micro Small and Medium Enterprises in Indonesia - Mulyati, Etty; Murwadji, Tarsisius (Jurnal IUS Kajian Hukum dan Keadilan, 2025)
The existence of marketplaces helps MSMEs expand their business reach and facilitates their transformation into digital MSMEs. However, issues have emerged concerning private marketplace platforms in Indonesia, particularly related to the increasing commission fees and direct-to-consumer sales by producers that bypass traditional distribution channels, disadvantaging smaller businesses. This raises the question of how local governments, as part of the welfare state, can establish and regulate marketplaces to empower MSMEs. The research method used is normative legal research with a statutory approach. The results of the study show that in accordance with the welfare state principle, the government bears responsibility for the economic welfare of its citizens. Local governments play a crucial role in supporting MSMEs by developing regionally owned marketplaces. These platforms implement policies such as differentiated commission rates based on the scale of the business, where smaller enterprises are subject to lower fees, and allow only MSME-scale producers and those selling perishable goods to conduct direct sales. These measures are intended to provide fairer access and greater protection for micro small and medium enterprises within the digital economy.